Digital Marketing Literacy and MSMEs Improvement Based On The Teachings Of Ki Hadjar Dewantara: “Ngandel, Kendel, Kandel, and Bandel" - Agus Dwi Cahya; Nanang kususma mawardi; dika Prawita; chichi; seliana Intan Tri; Miraldi (IMPACTS: International Journal of Empowerment and Community Services, 2022)
This study aims to overcome problems in the community, especially how to increase MSMEs and the importance of digital marketing literacy. This research stage is using the survey stage, identification and overcoming and implementation stages. The result is that many housewives have problems with increasing MSMEs and digital marketing. To overcome the above, socialization and introduction of digital marketing and the improvement of MSMEs were held with the teachings of KHD.